2017
DOI: 10.1038/s41598-017-14584-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective Colorimetric Detection of Nitrite in Water using Chitosan Stabilized Gold Nanoparticles Decorated Reduced Graphene oxide

Abstract: Excess nitrite (NO2 -) concentrations in water supplies is considered detrimental to the environment and human health, and is associated with incidence of stomach cancer. In this work, the authors describe a nitrite detection system based on the synthesis of gold nanoparticles (AuNPs) on reduced graphene oxide (rGO) using an aqueous solution of chitosan and succinic acid. The AuNPs-rGO nanocomposite was confirmed by different physicochemical characterization methods including transmission electron microscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Recently, researcher reported that F-GE is able of reducing tumor-cell growth in vivo and in vitro (Battogtokh et al,2017;Boyles et al,2015). In the present report, we have exposed for the first time that CSNPs coated F-GE/AuNPs xhibit drug delivery applications and determined the mechanism of action in different approaches (Osváth et al, 2015;Sayed et al, 2015;Yang et al, 2014;Hashemi et al,2017;Muddineti et al,2015;Duan et al,2014;Amanulla et al,2017;Bao et al,2015).…”
Section: Discussionmentioning
confidence: 76%
“…Recently, researcher reported that F-GE is able of reducing tumor-cell growth in vivo and in vitro (Battogtokh et al,2017;Boyles et al,2015). In the present report, we have exposed for the first time that CSNPs coated F-GE/AuNPs xhibit drug delivery applications and determined the mechanism of action in different approaches (Osváth et al, 2015;Sayed et al, 2015;Yang et al, 2014;Hashemi et al,2017;Muddineti et al,2015;Duan et al,2014;Amanulla et al,2017;Bao et al,2015).…”
Section: Discussionmentioning
confidence: 76%
“…Many probe-based sensors intended for on-site detection using organic chromophores, small fluorescent organic molecules [ 10 , 11 , 12 ], Quantum Dots (QDs) [ 13 , 14 ], conjugated polymers [ 15 ], and DNA-zymes [ 16 ] have been developed for fluorescent, colorimetric [ 17 , 18 , 19 ], and electrochemical detection of Ag + [ 20 , 21 ]. However, some drawbacks still exist, such as poor aqueous solubility [ 18 , 22 ], bad stability, low sensitivity, large physical size, complicated synthesis procedures, high toxicity, and cross-sensitivity toward other metal ions, especially to Hg 2+ [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is necessary to monitor and manage nitrate concentration in water using sensors for efficient and economic farming. Some researchers used graphene-based electrochemical sensing methods [45][46][47][48][49][50][51][52], whereas some researchers used the colorimetric [53] method for detecting nitrate in water samples. A summary of the existing nitrate sensors is included in Table 6.…”
Section: Parametermentioning
confidence: 99%